Development and implementation of a competency-based module for teaching research methodology to medical undergraduates - Somdatta Patra; Amir Maroof Khan (Journal of Education and Health Promotion, 2019)
CONTEXT: Research experience helps an undergraduate student to understand published works, to learn teamwork, and even to consider research as a career. Few medical institutions have attempted to engage undergraduates in research experience. Competency-based medical education has emerged as a core strategy to educate and assess medical students worldwide. AIMS: This study aims to develop and implement a competency-based research methodology training module for undergraduate students and find out students' perception about this. SETTINGS AND DESIGN: A cross-sectional study of mixed design was undertaken in the Department of Community Medicine, UCMS, Delhi, India. METHODOLOGY: A competency-based research training module was developed and implemented with 4th semester undergraduate students posted in the department. Students' feedback about the module was obtained. STATISTICAL ANALYSIS USED: For quantitative variables, means, ranges, medians, and percentages were calculated. To find out students' perception about the posting a qualitative analysis was done. RESULTS: The module was implemented with 25 students posted in the department in May 2017. However, feedback was obtained from 23 students. About 83% of the students reported as highly satisfied with the posting, 61% of the students mentioned that after completion of this posting, they felt motivated to do further research. A qualitative analysis of the feedback showed that students found the project helped them to enhance their knowledge and develop skills. CONCLUSIONS: Competency-based research methodology training can serve as a tool for teaching research methodology to undergraduate students.